Rumanian Slavia as the Frontier of Orthodoxy. The Case of the Slavo-Rumanian Tetraevangelion of Sibiu - Stabile, Giuseppe (Studia Ceranea, 2019)
At least from the 14th to the 17th c. – beyond their Middle Ages until their Early Modern Ages – the Rumanians belonged to the so-called Slavia Orthodoxa. Besides the Orthodox faith, they had in common with the Orthodox Slavs the Cyrillic alphabet until the 19th c. and the Church Slavonic, which was the language of the Church, of the Chancery and of the written culture, until the 17th c., although with an increasing competition of the Rumanian volgare. The crisis and decline of the Rumanian Slavonism, the rise of the local vernacular, have been related with Heterodox influences penetrated in Banat and Transylvania. Actually, the first Rumanian translations of the Holy Scriptures, in the 16th c., were promoted, if not confessionally inspired, by the Lutheran Reformation recently transplanted in Banat and Transylvania (some scholars incline to a [widely] Hussite origin of these early translations). Not only Banat and Transylvania, but also Moldavia and Wallachia (the Principalities) were crossed by the border between the Latin and the Byzantino-Slavonic world, the Slavia and the Romania. Influences from the whole Slavia – the Orthodox and the Latin Slavia, the Southern, the Eastern and the Western one – met in the Carpatho-Danubian Space describing what will be derogatively called Slavia Valachica (i.e. Rumanian): a kaleidoscope of Slavic influences in Romance milieu. The appearance of Slavo-Rumanian texts, either with alternate or parallel Church Slavonic and Rumanian, revealed that in the middle of the 16th c. the decline of Slavonism had already started. Mostly but not only in the western regions, beyond the Carpathians, which were under Latin rule, the Orthodox (“Schismatic”) clergy was less and less confident with the Slavonic. This last still remained the sacred language though largely unintelligible, whilst the vernacular still lacked sacred dignity, besides being suspect to spread Heterodoxy. The Slavo-Rumanian Tetraevangelion of Sibiu (1551–1553) is the oldest version of a biblical text in Slavonic and Rumanian and contains the oldest surviving printed text in Rumanian. Apart from evoking icastically – by its twocolumns a fronte layout – the Slavic-Rumanian linguistic border, this fragment of a Four-Gospels Book (Mt 3, 17 – 27, 55) can be considered in many senses a border text: geographically (the border between East and West), chronologically (the decline of Slavonism and the rise of the Rumanian Vernacular), culturally and confessionally (the border between the Latin [i.e. Catholic then Protestant too] West and the Byzantino-Slavonic East). This paper aims to reconstruct, as far as possible, the complex milieu in which the Tetraevangelion was translated, (maybe) redacted and printed, focusing on the Slavonisms in its Rumanian text. A special attention will be paid to any possible interaction between that mainly Latin (Lutheran-Saxon) milieu and the Rumanian Slavonism.